Palladium nanostructure incorporated cupric oxide thin film with strong optical absorption, compatible charge collection and low recombination loss for low cost solar cell applications. (April 2018) - Masudy-Panah, Saeid; Zhuk, Siarhei; Tan, Hui Ru; Gong, Xiao; Dalapati, Goutam Kumar
Abstract: Cupric oxide (CuO) is one of the most promising and low-cost materials for solar cell application, but its power conversion efficiency is limited by discrepancy between short carrier diffusion length and optical absorption length, low charge collection efficiency, and high recombination rate. We present a novel optical absorbing CuO film to simultaneously address all of these issues by combining thin films of palladium (Pd) nanoparticles-incorporated CuO (CuO:Pd), nitrogen-doped CuO (CuO:N), and nitrogen-doped cuprous oxide (Cu2 O:N). Incorporation of Pd nanoparticles significantly increases photo-generated charge collection efficiency and enhances optical absorption over the wide range of solar spectrum. Graded refractive index and step distribution of carrier concentration of Cu2 O:N/CuO:N thin films reduce optical reflectance and build high potential into optical absorbing thin film. The Cu2 O:N/CuO:N/CuO:Pd/CuO thin film increases charge collection efficiency and reduces recombination rates. Using this design, record high short circuit current density ( J sc ) and efficiency ( η ) of around 28.5 mA cm −2 and 8.3 are achieved, respectively, for heterojunction solar cell using Cu2 O:N/CuO:N/CuO:Pd/CuO thin film on titanium (Ti) passivated n-type silicon (Si) substrate ( p -(Cu2 O:N/CuO:N/CuO:Pd/CuO)/Ti/ n -Si). J sc and η for p -(Cu2 O:N/CuO:N/CuO:Pd/CuO)/Ti/ n -Si solar cell are around 14 and 40 times higher than the control p-CuO/n-Si solar cell, respectively. This work provides a novel approach to achieve high efficiency CuO-based thin film solar cells. Graphical abstract: Incorporation of Pd nanoparticles significantly increases photo-generated charge collection efficiency and enhances optical absorption over the wide range of solar spectrum. Graded refractive index and step distribution of carrier concentration of Cu2 O:N/CuO:N thin films reduce optical reflectance and build high potential into optical absorbing thin film. The Cu2 O:N/CuO:N/CuO:Pd/CuO thin film increases charge collection efficiency and reduces recombination rates. Using this design, record high short circuit current density ( J sc ) and efficiency ( η ) of around 29 mA cm -2 and 8.3 are achieved, respectively, for heterojunction solar cell using Cu2 O:N/CuO:N/CuO:Pd/CuO thin film on titanium (Ti) passivated n-type silicon (Si) substratefx1 Highlights: Palladium (Pd) nanostructure incorporated CuO (CuO:Pd) film and solar cells. Pd nanostructure to enhance light trapping and charge collection efficiency. CuO:Pd thin film with front surface field and Cu2 O:N hole transporting layer. Reduction of surface defects using titanium interface passivation layer. P-(CuO:Pd)/n-Si solar cells with short-circuit current of ~ 29 mA/cm 2 and efficiency of ~ 8.3%.